International Foundation for Science (IFS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
International Foundation for Science (IFS) There are many talented scientists from developing countries who, when they encounter difficulties in carrying out research in their own countries, either decide to emigrate or settle for an administrative...